PENGEMBANGAN WISATA OLAHRAGA DAN KEBUGARAN DALAM KAWASAN EKONOMI KHUSUS PARIWISATA TANJUNG KELAYANG BERBASIS POTENSI HUTAN DAN PESISIR - Pradhana, Arief (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study analyzes the potential for developing sport and wellness tourism based on forest and coastal resources in the Tanjung Kelayang Tourism Special Economic Zone (SEZ). The study employed a descriptive qualitative design supported by quantitative data. Data were collected through semi-structured interviews, field observation, and documentation, then analyzed using descriptive qualitative techniques, ADO-ODTWA potential assessment, and SWOT analysis. The results show that forest-based potential falls into the moderate category (52.08%), while coastal potential is high (83.33%). The strategic position lies in the diversification quadrant (ST), indicating that preserved environmental quality, coastal scenery, and forest landscape can support sport tourism and wellness tourism development. However, attraction design, accessibility, supporting facilities, and zoning clarity remain necessary to maintain environmental sustainability.